ЎСМИРЛИК ДАВРИДАГИ АГРЕССИВ ХУЛҚ – АТВОР ИЖТИМОИЙ – ПСИХОЛОГИК МУАММО СИФАТИДА - Кушанова, М.И. (SCIENCE and SOCIETY, 2021)
This article discusses the concepts of aggression and aggressive behavior that manifest themselves in adolescence, the views, definitions and positions of foreign and domestic scientists who have conducted scientific research in this field, as well as the fact that in modern society, scientific research conducted within the framework of psychological science shows that aggression occupies a leading place among the problems associated with human behavior.